2015
DOI: 10.1016/j.bbamem.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topology of NS2B of dengue virus revealed by NMR spectroscopy

Abstract: Non-structural (NS) proteins of dengue virus (DENV) are important for viral replication. There are four membrane proteins that are coded by viral genome. NS2B was shown to be one of the membrane proteins and its main function was confirmed to regulate viral protease activity. Its membrane topology is still not known because only few studies have been conducted to understand its structure. Here we report the determination of membrane topology of NS2B from DENV serotype 4 using NMR spectroscopy. NS2B of DENV4 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 56 publications
5
59
0
Order By: Relevance
“…These well-conserved residues have been proposed to be essential for RNA replication. In agreement with this observation, sequence alignment of the amino acid residues of the nonstructural proteins among DENV2, WNV KUN , YFV, and JEV revealed that NS1, NS2B, NS3, NS4A, NS4B, and NS5 were variably conserved (33,14,40,22,15, and 51% identity, respectively), while NS2A was the least conserved (8% identity) (data not shown). Similarly, strong conservation was observed in the NS1, NS2B, NS3, NS4A, NS4B, and NS5 (61, 42, 67, 53, 73, and 67% identity, respectively) proteins among the four dengue virus serotypes, while NS2A was the least conserved (18% identity).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These well-conserved residues have been proposed to be essential for RNA replication. In agreement with this observation, sequence alignment of the amino acid residues of the nonstructural proteins among DENV2, WNV KUN , YFV, and JEV revealed that NS1, NS2B, NS3, NS4A, NS4B, and NS5 were variably conserved (33,14,40,22,15, and 51% identity, respectively), while NS2A was the least conserved (8% identity) (data not shown). Similarly, strong conservation was observed in the NS1, NS2B, NS3, NS4A, NS4B, and NS5 (61, 42, 67, 53, 73, and 67% identity, respectively) proteins among the four dengue virus serotypes, while NS2A was the least conserved (18% identity).…”
Section: Discussionsupporting
confidence: 55%
“…10. Interestingly, the second dominant reversion mutation, NS2B-I114T, is located in the fourth pTMS close to the ER lumen side (33). Several defective NS2A mutants located in pTMS1, pTMS2, pTMS3, and pTMS4 were rescued by NS2B-I114T, implicating the intricate protein complex formed by the pTMSs within NS2A and NS2B.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, each of the four TMD helices contains a small-XXX-small motif ("small" represents amino acids with small side chains [Gly, Ala, and Ser], and "X" represents any amino acid) that is important for TMD-TMD interactions. Such structural characteristics of NS2B might confer more freedom to induce conformational changes in membranes under different conditions, facilitating interaction with other viral membrane proteins through its TMDs (15). Indeed, using fluorescent resonance energy transfer (FRET)-and biomolecular fluorescent complementation (BiFC)-based imaging methods, Yu et al showed that WNV NS2B could interact with itself, as well as most other NS proteins, including the other three membrane proteins, NS2A, NS4A, and NS4B (16).…”
mentioning
confidence: 99%
“…It is currently unclear how the NS2B TMDs regulate flaviviral replication. A recent nuclear magnetic resonance (NMR) study revealed the membrane topology of DENV4 NS2B (15). The hydrophilic cofactor region forms a ␤-strand structure, while the TMDs contains four short helical segments.…”
mentioning
confidence: 99%